Growing Cd₀.₂₅Hg₀.₇₅Se layers by laser evaporation in static vacuum - Gritsook, B.N.; Fodchoock, I.M.; Nichiy, S.V.; Paranchich, U.S.; Politanskiy, R.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Cd₀.₂₅Hg₀.₇₅Se films received by laser evaporation method in conditions of static vacuum are investigated. Optimum temperature of a substrate is ascertained using structural and electrophysical measurements. It is shown that the used method enables one to receive films of CdxHg₁₋xSe solid solutions close to bulk material by their properties.